Nutritive value of Crotalaria ochroleuca: I. Chemical composition and in vitro dry matter digestibility at different stages of growth - Mkiwa, F.E.J.; Sarwatt, S.V.; Lwoga, A.B.; Dzowela, B.H. (International Livestock Centre for Africa, 1990)
Reports on the initial stages of a work carried out to evaluate the nutritive value of Crotalaria ochroleuca (marejea). Determines dry matter yield, chemical composition and invitro dry matter digestibility. Examines DM & OM contents and yields, chemical compostion with whole plant, leaf and stem and in vitro DM digestibility of plant parts of "marejea" with advanced plant growth.